The Economic Consequences of Legal Origins - Porta, Rafael La; Lopez-de-Silanes, Florencio; Shleifer, Andrei (Journal of Economic Literature, 2008)
In the last decade, economists have produced a considerable body of research suggesting that the historical origin of a country's laws is highly correlated with a broad range of its legal rules and regulations, as well as with economic outcomes. We summarize this evidence and attempt a unified interpretation. We also address several objections to the empirical claim that legal origins matter. Finally, we assess the implications of this research for economic reform.